2020
DOI: 10.1111/jcal.12437
|View full text |Cite
|
Sign up to set email alerts
|

Linking learner factors, teaching context, and engagement patterns withMOOClearning outcomes

Abstract: Prior studies of MOOC learners have focused almost exclusively on behavioural and social aspects of engagement. This paper extends the scope of previous studies by adopting a multi‐dimensional, person‐centred approach to investigate learner engagement in MOOCs. An analysis of 1,452 self‐administered survey responses uncovered three prototypical categories of MOOC learners based on patterns of behavioural, cognitive, emotional and social engagement: (a) “Individually Engaged” learners, (b) “Least Engaged” learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 93 publications
2
32
0
Order By: Relevance
“…MOOCs grades, behavioral (Phan et al, 2016) outcomes and social engagement were found to have favorable connections (Gillani & Eynon, 2014;Torres & Beier, 2018). According to these studies, educators and learning designers are encouraged to include learning activities in MOOCs relevant to career demands, in order to increase learners' extrinsic motivations (Deng et al, 2020). In this report, the researchers also said that learners' engagement might be further stimulated by cognitively engaging the course and by inserting suitable formative assessment into such tasks.…”
Section: Learning With Moocsmentioning
confidence: 97%
See 1 more Smart Citation
“…MOOCs grades, behavioral (Phan et al, 2016) outcomes and social engagement were found to have favorable connections (Gillani & Eynon, 2014;Torres & Beier, 2018). According to these studies, educators and learning designers are encouraged to include learning activities in MOOCs relevant to career demands, in order to increase learners' extrinsic motivations (Deng et al, 2020). In this report, the researchers also said that learners' engagement might be further stimulated by cognitively engaging the course and by inserting suitable formative assessment into such tasks.…”
Section: Learning With Moocsmentioning
confidence: 97%
“…Learners worldwide have benefitted from MOOCs (Sidek et al, 2019;Gabaree et al, 2020;). During the Covid-19 pandemic, learners were able to evaluate their courses at home.…”
Section: Learning With Moocsmentioning
confidence: 99%
“…Reason cited was not adequate users of MOOCs available in their sampling frame to carry out probability sampling (Alraimi et al, 2014;Shapiro et al, 2017). Non-probability sampling method used by the majority of researchers may skew sample representations and therefore the generalizability of research findings (Stich & Reeves, 2016) hence a strong need to apply probability sampling method to collect data (Deng et al, 2020;Mulik et al 2018) to generalize research findings.…”
Section: Over Dependence On Quantitative Techniquesmentioning
confidence: 99%
“…The classification of engagement styles is based on what activities are undertaken and how often they are participated in by a learner throughout the course [30]. Studies [31][32][33] have demonstrated contradictory results regarding performance by learners with different engagement styles. On the one hand, the more learners engage with course activities, the better they perform [7].…”
Section: Engagement Styles and Performancementioning
confidence: 99%